The Place of “asma Al-husna” (Beautiful Names of Allah) in Islamic Research - Rahnulla, Yegana (Scholarya Demo Journal of Ruby, 2020)
“Asma al-husna” is a religious term expressing 99 most beautiful names of God taken from different ayahs and hadiths of Quran. Inspired by these ayahs and hadiths, most Islamic scholars wrote valuable works and attracted researchers’ attention to “Asmaul-husna” as one of the important subjects of theology. Most Islamic scholars comprehensively expalined this with special emphasis on the hadith narrated by Abu Hureyra Abdurrahman b. Sahr adDavsi as well as the classification of “Asma al-husna” which includes beautiful names of Allah. In the religious literary sources there are different notes related to God’s 99 names entered into “Asma al-husna”. This article involves the brief information of the works written about “Asma al-husna” up to now. The works or books written and published in the Arabic, Persian, Turkish, Azerbaijani and many other languages have been studied and presented in chronological order. Besides the works of the famous Islamic scholars, the books translated into different languages have also been researched. The Institute of Manuscripts named after M.Fuzuli of ANAS preserves the manuscripts of the works on different fields of theology written by wellknown Islamic scholars and thinkers. Dealing with the nice names of Allah, “Asma al-husna” takes a particular place among the works on theology preserved in the Institute of Manuscripts named after M.Fuzuli of ANAS. This research uses not only modern publications, but also the old Azerbaijani manuscripts.